2014
DOI: 10.1002/cncr.28817
|View full text |Cite
|
Sign up to set email alerts
|

When performance management works: A study of theNationalBreast andCervicalCancerEarlyDetectionProgram

Abstract: BACKGROUND: Little empirical evidence exists about the effectiveness of performance management systems in government. This study assessed the effectiveness of the performance management system of the National Breast and Cervical Cancer Early Detection Program (NBCCEDP) and explored why it works. METHODS: Generalized estimating equation models were used to assess change in program performance after the implementation of a performance management system. In addition, qualitative case study data including observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…This policy recommendation was made before the national recommendations were changed in 2002 to wait 3 years between screenings [18]. In 2005, NBCCEDP policy was incorporated as a core indicator within a CDC-administered performance management system to prioritize funding resources for NR women, with a goal that at least 20 % of women newly enrolled in the NBCCEDP for cervical screening should be NR [19]. Our data indicated that most NR women who came to the NBCCEDP were aged ≥50 years, white, Asian–Pacific Islander, American Indian/Alaskan Native, or multiracial, and were living in nonmetro areas and in the South or a territory.…”
Section: Discussionmentioning
confidence: 99%
“…This policy recommendation was made before the national recommendations were changed in 2002 to wait 3 years between screenings [18]. In 2005, NBCCEDP policy was incorporated as a core indicator within a CDC-administered performance management system to prioritize funding resources for NR women, with a goal that at least 20 % of women newly enrolled in the NBCCEDP for cervical screening should be NR [19]. Our data indicated that most NR women who came to the NBCCEDP were aged ≥50 years, white, Asian–Pacific Islander, American Indian/Alaskan Native, or multiracial, and were living in nonmetro areas and in the South or a territory.…”
Section: Discussionmentioning
confidence: 99%
“…Articles gathered during the search described research conducted in many countries around the world. Six studies were carried out in Brazil [13,14,15,16,17,18] and four in the United States [19,20,21,22] . There was only one article from each of the following countries: Argentina [23] , Australia [24] , Canada [25] , England [26] , Italy [27] , Malawi [28] , Zambia [29] and United Kingdom [30] .…”
Section: Characterizing the Studiesmentioning
confidence: 99%
“…The performance of grantees has improved since the introduction of the data feedback and quality-assurance reports along with other performance management strategies. 11 …”
Section: Introductionmentioning
confidence: 99%